Multi-Verse Optimizer for LFO Damping in Single Machine Infinite Bus Power Networks - Hasan, Abdul Majid; Islam, Md. Rashidul; Shafiullah, Md; Uddin, Md Burhan (2022 International Conference on Advancement in Electrical and Electronic Engineering (ICAEEE), 2022)
The power system is an extremely nonlinear structure with complicated characteristics. Power networks are electrically intertwined and they are susceptible caused by disruptions in anyone part of the system. In fact, low frequency oscillations (LFOs) caused by minor perturbations in any portion of the network might bring the entire system down. With the appropriate parameter settings, the power system stabilizer (PSS) effectively reduces these oscillations. This paper proposes a completely unique nature algorithm, to tune PID and Lead-Lag based controller using Multi-Verse Optimizer (MVO) for SMIB system to control LFOs by improving power system damping. By comparing simulation results with fixed gain traditional PSS, the performance of the MVO tuned PSS is analyzed. Furthermore, comparing between MVO and Genetic Algorithm based tuned PSS, eigenvalues and the damping ratio of the same network were evaluated.